Swift for TensorFlow - Bailey, Paige; Saeta, Brennan (O'Reilly Media, Inc., 2020)
Swift for TensorFlow is a next-generation machine learning platform that leverages innovations like first-class differentiable programming to seamlessly integrate deep neural networks with traditional AI algorithms and general purpose software development. Paige Bailey and Brennan Saeta (Google) demonstrate how Swift for TensorFlow can make advanced machine learning research easier and faster. Prerequisite knowledge Experience with ML development General knowledge of Swift (useful but not required) What you'll learn See how Swift for TensorFlow can change the way you think about ML.